Multicentric reticulohistiocytosis with pure cutaneous involvement - Basavapura Madegowda Shashi Kumar; Somaiah A Savitha; Katwe Kirti (Wolters Kluwer Medknow Publications, 2020)
Multicentric reticulohistiocytosis is a rare type of non-Langerhans cell histiocytosis. The typical lesions include skin involvement with erosive arthritis. Diagnosis is confirmed by the presence of histiocytes and multinucleated giant cells. About 15%-30% of cases are associated with malignancy. Here, we report a case of an 18-year-old boy who presented with sudden onset of brown asymptomatic lesions on the face and back of 2 months' duration, which on biopsy showed dense infiltrate of histiocytes and giant cells. However, he did not have any symptoms of systemic involvement and all routine investigations were normal. The lesions have not progressed on 1 year of follow-up.